Estudo fitoquímico pioneiro de Pavonia cancellata (L.) - Malvaceae - Fernandes, Milen Maria Magalhães de Souza (2013)
The use of plants to control of various diseases and pests is as old as the appearance of humanity. Nowadays, many medicinal plants and its preparations are studied in order to understand its action mechanism and isolation of active principles. Regarding the diversity of Brazilian flora we aimed to isolate and identify the chemical constituents of Pavonia cancellata (L.) through a pioneer phytochemical study. Pavonia cancellata (L.) belongs to Malvaceae family that has been known by the use of its species in folk medicine. The leaves of Pavonia cancellata (L.) popularly known as corda de viola or malva rasteira are used as a poultice to boils treatment. By using classical chromatographic techniques were isolated four chemical constituents from crude ethanol extract of the aerial parts of Pavonia cancellata ( L. ): a mixture of sitosterol (Pc-1a) and stigmasterol (Pc-1b), a mixture sitosterol-3-O-β-D-glucopyranoside (Pc- 2a) and stigmasterol-3-O-b-D-glucopyranoside (Pc-2b), 4 5-di-hyidroxy- 3,7- dimethoxiflavone (Pc-3) and kaempferol-3-O-b-D-(6 -E-p-coumaroyl) glucopyranoside (Pc-4). The structural identification of these compounds was performed using spectroscopic methods such as Infrared and 1H and 13C Nuclear Magnetic Resonance